In search of inspiration: Psychoactive substances in jazz history - V. Yu. Skryabin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Throughout the history of jazz, its close association with psychoactive substances has been one of the most controversial and debated topics. From the smoke-filled clubs of the 1920s, where attendees smoked marijuana freely, to the underground jam sessions of the 1960s, where heroin reigned supreme, the lifestyles of jazz musicians have often included illicit substances. The careers of many talented jazz musicians have been sidelined or prematurely cut short due to addiction to drugs and/or alcohol. The lives of the most famous of them, from Louis Armstrong and Milton Mezzrow to Charlie Parker, Billie Holiday, Miles Davis, and Chet Baker, attest to the significant place of psychoactive substances in jazz folklore.The aim of the work: to conduct a narrative review of the available literature on the influence of SAW on the lives and work of jazz musicians.Method: this article presents a narrative review of the foreign literature on the place of psychoactive substances in the history of jazz music. Articles in MEDLINE/PubMed and Scopus databases, as well as monographs and biographies of musicians were selected and analyzed. The search was conducted using different variants of the specified keywords.Results: heavy long night performances, frequent relocations, and for many musicians the disapproving attitude of the society had its own imprint on the creativity of many representatives of the genre. Concerts in conditions of availability of surfactants and general loyalty to their use, psychological pressure associated with the need to maintain a high level of performance skills against the background of constant competition, the impact of negative social factors were risk factors that contributed to the development of addiction. If at the first stages of jazz development drugs served as a kind of tonic from the torments faced by a jazz musician in everyday life, then later they were transformed into an important component of the jazzist’s identity and a means of distinguishing the jazz community.Conclusion: artists such as Coleman Hawkins, Lester Young, Bud Powell, Charlie Parker, Billie Holiday, Miles Davis, Sonny Rollins, and John Coltrane struggled with substance abuse at some point in their careers. Interestingly, these same names are often mentioned by critics when listing the great innovators and most influential performers in the history of jazz music. It is noteworthy that in the modern period, jazz has ceased to be the center of countercultural drug use. In the 1960s and 70s, the drug legacy of jazz passed first to rock and roll and then to hip-hop.